Estimated Shelf Life Beverage Powders Sea Slug (Discodoris sp.) with Accelerated Shelf Life Test (ASLT) Method: Arrhenius Model - Putri, Raja Marwita Sari; Nurjanah, Nurjanah; Tarman, Kustiariyah (Marinade, 2018)
The Arrhenius model ASLT method is widely used to estimate the shelf life of food products that are easily damaged by the effects of chemical reactions, including fat oxidation, Maillard reactions, protein denaturation and so on. The aim of this study was to determine the best shelf life through stability testing. Testing shelf life was done by acceleration time or acceleration model using Arrhenius method. During the storage period, the product was stored in three different temperature conditions, ie, 30 Â° C, 35 Â° C and 45 Â° C. Stability test performed on every 7 days observation of water content test (aw). Estimation of shelf life based on the critical parameter that is water activity value (aw) hence can be known save age of functional beverage powders sea slug of T2 have a longer shelf life when compared with  T1.